Study of properties of firmness of solutions of equations with partial derivatives by the method of separation of variables - Bugir, M. K. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
The oscillatory character of solutions of partial differential equations is studied by the method of separation of variables; an ill-posed boundary value problem for a fourth-order polyharmonic equation, where the boundary conditions are given on two rectangles embedded one in the other, is studied; bounds for conditional stability and regularization are established.